Balanced nutrition education to prevent stunting in children - Yani Maidelwita; Yoga Tri Wijayanti; Nurafriani Nurafriani; Indryani Indryani; Heni Selvia; Tri Maya Cahya Mulat (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2024)
Stunting is a condition in which a child has a lower height than their standard age, which can be caused by chronic malnutrition. This community service aims to educate children about balanced nutrition to prevent stunting. The methods used in this program include direct counseling, distribution of informative brochures, and demonstrations of the presentation of nutritious food. The target of the program is parents, especially mothers who have children under the age of five. The activity results showed increased participants' knowledge and awareness of the importance of balanced nutrition in child growth. The conclusion is that this community service program has succeeded in increasing public understanding and awareness of the importance of balanced nutrition in preventing stunting in children. This can be seen from the increase in the participants' knowledge about balanced nutrition and the steps that must be taken to ensure that children get enough food. In addition, this program has also succeeded in encouraging behavioral changes in the diet of participants' families, which is expected to contribute to reducing stunting rates in the area. With continuous education and support from various parties, it is hoped that stunting prevention efforts can run more effectively and children can grow healthy and optimally.